PENENTUAN RECEIVED DATE DENGAN LOAD-ORIENTED MANUFACRURING CONTROL - Hartini, Sri; Sriyanto, Sriyanto; Karima, Naela (J@ti Undip : Jurnal Teknik Industri, 2008)
Salah satu kunci kompetitif sebuah perusahaan make to order adalah ketepatan dalam pemenuhan waktu penerimaan pesanan pada konsumen yang telah dijanjikan perusahaan ( received date). Penentuan received date yang selama ini dilakukan oleh JI  kurang tepat karena hanya memperkirakan waktu sekitar 10 – 12 minggu tanpa mempertimbangkan faktor produksi. Penelitian ini merancang received date dengan model load-oriented manufacturing control dimana penentuan received date didasarkan pada perhitungan manufacturing lead time yang mempertimbangkan waktu pengiriman order ke konsumen, kapasitas yang tersedia pada tiap stasiun kerja, waktu proses pada stasiun kerja dan aliran produksi di lantai produksi. Hasil validasi perhitungan  penentuan received date order sesuai  dengan sistem produksi PT JI dan lebih valid dibanding sistem awal. Kata kunci : make to order, received date, manufacturing leadtime, load-oriented manufacturing control  One of the competitive key of a make to order company is the accuracy in fulfilling orders which has been promised by the company towards the consumers (received date). Determining received date which has been applied by JI recently is not sufficient because it only predicts 10-12 weeks of time without considering production factors. This research designs received date with load-oriented manufacturing control model where determining received date is based on calculating manufacturing lead time that considers the time needed to deliver orders to the consumer, capacity available for each work station, work station process time, and production flow within the production floor.  Validation results from the calculations for determining received date order is adjusted to PT JI  production system and is more valid than the first system. Keywords : make to order, received date, manufacturing leadtime, load-oriented manufacturing control